On a critical Choquard-Kirchhoff p-sub-Laplacian equation in ℍn - Liang Sihua; Pucci Patrizia; Song Yueqiang; Sun Xueqi (Analysis and Geometry in Metric Spaces, 2024)
This article is devoted to the study of a critical Choquard-Kirchhoff pp-sub-Laplacian equation on the entire Heisenberg group Hn{{\mathbb{H}}}^{n}, where the Kirchhoff function KK can be zero at zero, i.e., the equation can be degenerate, and involving a nonlinearity, which is critical in the sense of the Hardy-Littlewood-Sobolev inequality. We first establish the concentration-compactness principle for the pp-sub-Laplacian Choquard equation on the Heisenberg group, and we then prove existence results.